Proceedings of the Singaporean-French IPAL Symposium 2009 : SinFra '09 : 18-20 February 2009, Singapore. - Leow, Wee-Kheng, 1961- (World Scientific Pub. Co., 2009)
Proceedings of a symposium held to promote research collaboration between French and Singapore scientists in the area of image perception, access & language (IPAL).